The Enzymatic Conversion of Major Algal and Cyanobacterial Carbohydrates to Bioethanol - Al Abdallah, Qusai; Nixon, B. Tracy; Fortwendel, Jarrod R. (Frontiers in Energy Research, 2016)
The production of fuels from biomass is categorized as first-, second- or third-generation depending upon the source of raw materials, either food crops, lignocellulosic material, or algal biomass, respectively. Thus far, the emphasis has been on using food crops creating several environmental problems. To overcome these problems, there is a shift toward bioenergy production from non-food sources. Algae, which store high amounts of carbohydrates, are a potential producer of raw materials for sustainable production of bioethanol. Algae store their carbohydrates in the form of food storage sugars and structural material. In general, algal food storage polysaccharides are composed of glucose subunits, however they vary in the glycosidic bond that links the glucose molecules. In starch-type polysaccharides (starch, floridean starch, and glycogen), the glucose subunits are linked together by α-(1→4) and α-(1→6) glycosidic bonds. Laminarin-type polysaccharides (laminarin, chrysolaminarin, and paramylon) are made of glucose subunits that are linked together by β-(1→3) and β-(1→6) glycosidic bonds. In contrast to food storage polysaccharides, structural polysaccharides vary in composition and glycosidic bond. The industrial production of bioethanol from algae requires efficient hydrolysis and fermentation of different algal sugars. However, the hydrolysis of algal polysaccharides employs more enzymatic mixes in comparison to terrestrial plants. Similarly, algal fermentable sugars display more diversity than plants, and therefore more metabolic pathways are required to produce ethanol from these sugars. In general, the fermentation of glucose, galactose, and glucose isomers is carried out by wild type strains of Saccharomyces cerevisiae and Zymomonas mobilis. In these strains, glucose enters glycolysis, where is it converted to pyruvate through either Embden-Meyerhof-Parnas pathway or Entner-Doudoroff pathway. Other monosaccharides must be converted to fermentable sugars before entering glycolysis. In contrast, microbial wild type strains are not capable of producing ethanol from alginate, and therefore the production of bioethanol from alginate was achieved by using genetically engineered microbial strains, which can simultaneously hydrolyze and ferment alginate to ethanol. In this review, we emphasize the enzymatic hydrolysis processes of different algal polysaccharides. Additionally, we highlight the major metabolic pathways that are employed to ferment different algal monosaccharides to ethanol.